An explorative study with convenience vegetables in urban Nigeria - The Veg-on-Wheels intervention - Snoek, Henriette M.; Raaijmakers, Ireen; Lawal, Oruranti M.; Reinders, Machiel J. (2022)
Nigerian consumers have been found to view vegetables as healthy and health is a principal motivation for consumption; however, consumers also experience barriers related to preparation time and availability of vegetables. We therefore conducted a Veg-on-Wheels intervention, in which ready-to-cook, washed and pre-cut green leafy vegetables (GLV) were kept cool and sold for five weeks at convenient locations near workplaces and on the open market in Akure, Nigeria. Surveys were conducted prior to the intervention with 680 consumers and during the final week of the intervention with 596 consumers near workplaces and 204 consumers at the open market. Both buyers and non-buyers of the intervention were included; 49% buyers in the workplace sample and 47% in the open market sample. The Veg-on-Wheels intervention was successful, with high awareness, positive attitudes and high customer satisfaction. GLV intake was higher for Veg-on-Wheels buyers compared with non-buyers after the intervention, i.e., 10.8 vs. 8.0 portions per week, respectively. Also the intake of other vegetables was higher in the intervention group. The motives and barriers for buyers and non-buyers differed across the selling locations: main barriers were trust in the vendor and GLV source. These trust issues and vendor preferences were viewed as more important to respondents at the market than those near workplaces. This study is the first intervention study on the selling of ready-to-cook convenience vegetables in urban Nigeria. It shows that a market exists for convenience vegetables and that they have the potential to increase vegetable intake. Insights on both the food environment and consumers’ motives and behaviour was crucial for designing and evaluating the intervention.